Effect of Chlorotriphenyl Derivatives of Sn and Pb upon Biophysical Properties of Membranes. (21st June 2009) - Man, Dariusz; Podolak, Marian; Engel, Grzegorz; Boniewska, Ewa
Abstract : Biophysical activity of two twin organometallic compounds Triphenyltin chloride (TPhT) and Triphenyllead chloride (TPhL) in their interreaction with model membranes, as well as with yeast cells Saccharomyces cerevisiae, was investigated. Four measurement methods were used in the experiments: two physical methods (spin probes method and the electric method); two biological methods (minimal inhibitory concentration /MIC/ and yeast survival test). It has been found that the activity of TPhT in interaction with model membranes and yeast cells is distinctly greater than that of TPhL. The activity manifests itself by considerable increase in the fluidity of the middle part of liposome bilayer, change in the polarization direction of the transmembrane voltage of filters impregnated with lauric acid, and in complete inhibition of growth of yeast cells at the concentration of 5 μ g / mL .